1986
DOI: 10.1136/pgmj.62.733.1001
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid, serum glucose and diabetes: relationships in a population study

Abstract: Summary:The relationships between serum uric acid, serum glucose and diabetes have been examined in a survey of 7735 middle-aged men drawn at random from general practices in 24 British towns. There was a positive relationship between serum glucose and serum uric acid concentrations up to about 8.0 mmol/l; at higher levels of glucose, serum uric acid decreased. Uric acid levels were significantly reduced in insulin-dependent diabetics and in those on oral hypoglycaemics and also in 'non-diabetics' with casual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
88
3
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 13 publications
7
88
3
2
Order By: Relevance
“…Moreover, higher urate concentrations in prediabetic compared with non-diabetic subjects have also been reported." This work was indirectly confirmed by Cook et al,5 who showed that in a population study of men the mean urate concentrations increased with increasing mean glucose concentration until a mean glucose of approximately 8 mmollL was reached, after which the urate value did not increase further. Then as the mean glucose value increased above 10 mmollL there was a significant decrease in urate concentrations.…”
supporting
confidence: 74%
“…Moreover, higher urate concentrations in prediabetic compared with non-diabetic subjects have also been reported." This work was indirectly confirmed by Cook et al,5 who showed that in a population study of men the mean urate concentrations increased with increasing mean glucose concentration until a mean glucose of approximately 8 mmollL was reached, after which the urate value did not increase further. Then as the mean glucose value increased above 10 mmollL there was a significant decrease in urate concentrations.…”
supporting
confidence: 74%
“…Cook et al explained higher mean serum uric acid values in prediabetic patients than in recently diagnosed diabetics and lower values in diabetics. The negative association could be due to the increased excretion of uric acid during hyperglycemia and glycosuria [19]. In this study, triacylglycerol was increased in 46% of the total diabetic people.…”
Section: Discussionmentioning
confidence: 70%
“…GLU, as the sole nitrogen and carbon source, is in dynamic equilibrium in the human body and remains relatively constant under normal circumstances. The levels of GLU also have been shown to influence renal uric acid excretion during hyperglycemia and glycosuria (Christensen and Steenstrup, 1958;Cook et al, 1986). Interestingly, relationships have previously been observed between serum UA and serum glucose in subjects with gout (Beckett and Lewis, 1960).…”
Section: Discussionmentioning
confidence: 94%